Efektivitas Pendekatan TPACK dalam Meningkatkan Kemampuan Berpikir Kritis Guru di Daerah 3T: Studi Kuasi-Eksperimen di Sumba Barat Daya - Basori Basori; Zuhdi Zuhdi; Nuril Nuzulia; Sarkowi Sarkowi (CV. Creative Tugu Pena, 2026)
Teachers’ critical thinking is a core 21st-century competency, yet its development in Indonesia’s frontier, outermost, and underdeveloped (3T) areas remains constrained by a persistent digital divide and limited professional training. This study examined the effectiveness of the Technological Pedagogical Content Knowledge (TPACK) approach in enhancing six dimensions of teachers’ critical thinking according to Facione’s framework, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. A non-equivalent posttest-only quasi-experimental design was employed with two intact groups selected through cluster sampling: twenty teachers from MI Al Falah Sumba Barat Daya (experimental group) and twenty teachers from SDN Watu Takula (control group). Baseline equivalence was established through an equivalence test of demographic and professional characteristics. Data were collected using a ten-item essay test (Cronbach’s α = 0.87; CVI = 0.92) and a 24-item response questionnaire (Cronbach’s α = 0.84), both validated by three educational experts. Analyses included descriptive statistics, Kolmogorov-Smirnov normality test, Levene’s homogeneity test, and independent-samples t-test with Cohen’s d effect size. Results revealed a highly significant difference between the experimental group (M = 79.73, SD = 8.87) and the control group (M = 67.81, SD = 12.13), t(38) = 3.62, p < 0.001, with a large effect size (Cohen’s d = 1.13). The sharpest gains were observed in analysis (Δ = 32.68) and explanation (Δ = 19.48), while self-regulation showed the smallest gain (Δ = 4.50), attributable to the region’s limited reflective culture and digital infrastructure. This study contributes theoretically by extending the TPACK framework into low-resource contexts and practically by offering a replicable, low-cost TPACK training model for 3T regions in Indonesia and similar low- and middle-income settings.